DESIGN STUDY OF GAS COOLED FAST REACTOR WITH MODIFIED CANDLE BURNUP STRATEGY - MUSYAFAK (NIM: 20214058), AKHMAD
This research studied effects of reactor thermal power, fuel volume fraction change and materials of fuel to neutronic performances, for example burnup level, infinite multiplication factor, instantaneous conversion ratio, atomic number densities, and effective multiplication factor. Gas cooled Fast Reactor with Modified CANDLE burnup strategy is used. This study compared two kind of fuel, UN and U-10%Zr. Cladding material is Stainless Steel 316 and coolant material is helium. Pin cell calculation is ran by SRAC code version 2002 with data library from JENDL 3-2. Reactor core calculation is ran by FI-ITB CH1 program and used midnight commander (MC). Thermal power varied from 800 MW to 1300 MW with interval 100 MW. Fuel volume fraction varied from 50% to 65% with interval 2.5%. Calculation results show that thermal power and fuel volume fraction change and material of fuel effected to neutronic performances.